The Constructions and Pyrolysis of 3D Kerogen Macromolecular Models: Experiments and Simulations. Issue 5 (7th April 2019) - Wang, XiaoHe; Huang, XianFu; Lin, Kui; Zhao, Ya‐Pu
Abstract: Kerogens are extracted from deep shales to study pyrolysis of deep shale samples. The 2D molecular models of kerogens are obtained by a series of physical and chemical experiments by which the macromolecular models of kerogens are constructed. Then, the reasonable 3D macromolecular models are established by molecular mechanics and global energy minimization. The effects of temperature and heating rate on the chemical kinetics of kerogen pyrolysis are studied using reactive force field (ReaxFF). The hybrid molecular dynamics/force‐biased Monte Carlo (MD/fbMC) approach is used to simulate the pyrolytic process at the experimental temperature, which is lower than the conventional one. The gaseous products and residues obtained by the simulations agree with the experimental results, which means a reliable simulation method for pyrolysis at experimental temperature is provided. This study constructs the rational macromolecular models of kerogen by experiments, and proposes the mechanisms of typical reactions of kerogen pyrolysis, which may help in understanding the formation of shale oil and gas. Abstract : 3D kerogen macromolecular models are constructed by elemental analysis, X‐ray photoelectron spectroscopy, Fourier‐transform infrared spectroscopy, carbon‐13 nuclear magnetic resonance spectroscopy, and energy minimization. The models are large enough and their rationality is certified. Chemical kinetics of kerogen pyrolysis is analyzed by the reactive force field. The hybrid molecular dynamics/force‐biased Monte Carlo approach is used as a new method to study the kerogen pyrolysis, whose results are consistent with those of pyrolysis gas‐chromatogram and mass spectrogram.